VALUE OF NICOTINIC ACID IN THE CURRENT CARDIOLOGY - E. P. Trukhacheva; M. V. Ezhov (Рациональная фармакотерапия в кардиологии, 2016)
Statin intake is a standard in the treatment of patients with atherosclerosis nowadays. These drugs therapy associates with 30% risk reduction in mortality and coronary events. However , the threat of recurrent events is sufficiently high in large part of patients. This can be related to low level of high density lipoprotein cholesterol as well as elevated levels of triglycerides and lipoprotein(a). Nicotinic acid intake in these patients may be necessary for the normalization of lipid profile, including lipoprotein(a), and will be able to reduce residual cardiovascular risk. Evidence-based medicine data are presented to prove an efficacy of nicotinic acid in high doses in cardiology practice. Nicotinic acid both in monotherapy and in combination with statins contributes to coronary and carotid atherosclerosis regression and reduces an incidence of cardiovascular complications. Long-acting formulation of nicotinic acid, correct receiving regime and blood bio-chemical monitoring contribute to long-term safety of the drug in patients with clinically significant atherosclerosis.